Experimental investigation on the effect of initial pressure conditions during steam-water direct contact condensation in a horizontal pipe geometry. (February 2021) - Datta, Priyankan; Chakravarty, Aranyak; Saha, Ritabrata; Chaudhuri, Shouvik; Ghosh, Koushik; Mukhopadhyay, Achintya; Sen, Swarnendu; Dutta, Anu; Goyal, Priyanshu
Abstract: The present work reports an experimental investigation of direct contact condensation during subcooled water injection into a steam-filled horizontal pipe. The experiments have been carried out using a laboratory scale experimental facility that has been set-up in the Heat Power Laboratory of Jadavpur University. The experiments are carried out for two different initial steam pressure (2 and 3 bar) conditions and a pressure difference ranging from 1 to 3 bar between the water and steam sections. The pressure and temperature data are recorded at different salient locations within the test section. Temporal changes in temperature give an indication of water-front propagation within the test section. Observation reveals that no distinct pressure peak occurs when the pressure difference remains lowest, irrespective of the initial steam pressure within the test section. Distinct pressure peaks are, however, noticed at higher pressure differences. The amplitude of the pressure peaks is also observed to increase with the pressure difference. The maximum pressure peak amplitude, considering all the experiments, is observed to be approximately 6.08 bar at a distance of 1.51 m from the water inlet. These pressure peaks are attributed to the rapid collapse of vapour pockets when the corresponding locations become filled with subcooled water.